1994
DOI: 10.1002/jlb.55.6.711
|View full text |Cite
|
Sign up to set email alerts
|

The cooperative effects of TNF-α and IFN-γ are determining factors in the ability of IL-10 to protect mice from lethal endotoxemia

Abstract: Recent studies have demonstrated that interleukin-10 (IL-10) has the capacity to protect mice from the lethal effects of endotoxin. In this investigation, we have examined the ability of IL-10 to protect both normal mice and Corynebacterium parvum-primed mice against endotoxin lethality. In the overwhelming majority of experiments, recombinant murine IL-10 (rMuIL-10) and recombinant human IL-10 (rHuIL-10) did not protect normal BALB/cJ mice from lipopolysaccharide (LPS)-induced lethality at doses up to 10 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…Because IL-10 is a potent anti-inflammatory cytokine, it is possible that IL-10 has an important suppressive immunoregulatory role in the early stages of B. pseudomallei infection. Among its many activities, IL-10 inhibits the generation of nitrogen radicals in macrophages and suppresses proinflammatory cytokine production (37,45). In view of the results of the present study, it may be argued that the earlier appearance of IL-10 in spleen of BALB/c mice could lead to a preferential Th2-type cytokine response, diminished cell-mediated immunity, and increased host susceptibility.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Because IL-10 is a potent anti-inflammatory cytokine, it is possible that IL-10 has an important suppressive immunoregulatory role in the early stages of B. pseudomallei infection. Among its many activities, IL-10 inhibits the generation of nitrogen radicals in macrophages and suppresses proinflammatory cytokine production (37,45). In view of the results of the present study, it may be argued that the earlier appearance of IL-10 in spleen of BALB/c mice could lead to a preferential Th2-type cytokine response, diminished cell-mediated immunity, and increased host susceptibility.…”
Section: Discussionmentioning
confidence: 69%
“…Simultaneous increases in the levels of mRNA for IL-10 and IFN-␥, as observed in this study, are consistent with recent reports on cytokine responses to other intracellular pathogens (7,19,37). Such studies have suggested a potential beneficial role of IL-10 for increased host resistance during intracellular infection, despite the known anti-inflammatory actions of this cytokine (45). A cytokine pattern involving high levels of IL-10 and IFN-␥ without an increase in IL-2 or IL-4 has recently been coined the Tr1-type profile (22,30).…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6 In the present study, the pretreatment of mice with either anti-TNF-␣ MAb or anti-IFN-␥ MAb moderately, but not significantly, improved the hepatic microcirculation, whereas the combined use of two MAbs, even in half doses, increased the blood flow much more than did the controls and the treatment with a single MAb, which is indicative of the synergistic action of TNF-␣ with IFN-␥ for the induction of hemostasis. Cooperative activities of these cytokines have been reported also in the lethal endotoxemia 28 and cytokine-induced ischemic necrosis in many organs, including the lungs and liver. 27 Although it is unclear how TNF-␣ and IFN-␥ contribute to the hemostasis, they probably induce sinusoidal alterations such as endothelial swelling [15][16][17] and serotonin-mediated sinusoidal constriction 19,29 (IFN-␥ releases serotonin from the platelets 20 ).…”
Section: Discussionmentioning
confidence: 92%
“…We are unaware of any experimental or clinical data other than these that suggest successful intervention is possible in the later stages of the systemic inflammatory response (29). Current effective experimental treatment modalities for sepsis require either prophylactic treatment (30,31) or administration at the time of endotoxin challenge (32)(33)(34). Unlike these sepsis therapies, treatment with PGE1 plus liposomes takes advantage of the activation of professional phagocytes and thus exploits the natural cellular immune response to septic insult.…”
Section: Lpsmentioning
confidence: 99%